Lithuanian Old Personal Library Research: Status Quo - Braziūnienė, Alma (Bibliotheca Lituana, 2012)
The article analyzes the state of research on the old historical Lithuanian personal libraries, including the means of inquiry and sources. The author also analyzes the similarities between personal library research and institutional library research.It was found that book ownership marks are the main and most widely applicable personal library research source. This resource is used productively after Lithuanian scientific libraries have accelerated the scientific cataloging of the old books and started recording the provenance of each item (such catalogs include catalogs of the Elsevier, the Aldine, paleotypes, Bibliotheca Sapiehana by Vilnius University Library, Lituanica catalog by the Wroblewski Library of the Lithuanian Academy of Sciences, and the catalog of the 15th and 16th century books in Kaunas libraries by Kaunas County Public Library). The main and most widely applied Lithuanian historical personal library method is the provenance method, although good results are obtained using the hybrid method. The author concludes that most publications on old personal historic Lithuanian libraries limit their subjects to the personal libraries of nobility, state and religious actors (till the 19th Century) and the 19th century Lithuanian intellectuals. Historic personal libraries of lower-class individuals warrant more research (one example is Zigmantas Kiaupa’s publication about the book collections of ordinary old Kaunas’ citizens, published in 1985).
Keywords: none